Analisis Tingkat Kesehatan Perusahaan Berdasarkan Rasio Keuangan Pada PT Alkindo Naratama Tbk - Damayanti, Nuralvina; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial health of PT Akindo Naratama Tbk. for the 2015-2024 period using financial ratio analysis covering profitability, liquidity, and solvency. This study uses a quantitative descriptive approach using secondary data with data sources in the form of annual financial reports published through the Indonesia Stock Exchange (IDX). The results show that in the 2015-2021 period, the company showed a trend of improving performance with fairly good asset management efficiency. However, in the 2022-2024 period, the company experienced a significant decline in financial health in the third aspect. The liquidity ratio decreased to below the standard of 100% (illiquid), the solvency ratio showed a high debt dependence (above 90%), and profitability declined sharply by 0.4%. Overall, the financial health of PT Alkindo Naratama Tbk at the end of the study period was categorized as "Unhealthy", thus requiring a debt restructuring strategy and operational efficiency to restore financial performance in the future.